Eksperimen Pembelajaran Matematika Dengan Strategi Discovery Learning Berbasis Numbered Head Together (NHT) Dan Group Investigation (GI) Ditinjau Dari Kemampuan Awal Pada Siswa Kelas VII SMP Negeri 2 Banyudono - Yanti, Galih Ida; , Dra. N. Setyaningsih, M.Si; , M. Noor Kholid, M.Pd (2016)
This study aims to describe and analyze: (1) the difference between the effect of Discovery Learning strategy of Numbered Heads Together (NHT) and Group Investigation direct learning in mathematics learning outcomes, (2) the difference between the effect of prior knowledge direct learning in mathematics learning outcomes, (3) the interaction effect between Discovery Learning strategy of Numbered Heads Together (NHT) and Group Investigation in terms of prior knowledge direct learning in mathematics learning outcomes. The research was conducted students of VIII Grade of SMP N 2 Banyudono of even semester of academic year 2015/2016 with the population all students of VII a number of 267 students. Type of the research is experiment with quasi experimental design. The class sample of research by using the strastified cluster random sampling. Methods of data collection use documentation and test. Data analyzed by analysis of variance with two different cell lines. The results of data analysis with a significance level of 5% was obtained: (1) there is difference between the effect of Discovery Learning strategy of Numbered Heads Together (NHT) and Group Investigation direct learning in mathematics learning outcomes, (2) there is difference between the effect of prior knowledge direct learning in mathematics learning outcomes, (3) there is no interaction Discovery Learning strategy of Numbered Heads Together (NHT) and Group Investigation in terms of prior knowledge direct learning in mathematics learning outcomes.